Current state‐of‐art of STR sequencing in forensic genetics. Issue 21 (4th June 2018) - Alonso, Antonio; Barrio, Pedro Alberto; Müller, Petra; Köcher, Steffi; Berger, Burkhard; Martin, Pablo; Bodner, Martin; Willuweit, Sascha; Parson, Walther; Roewer, Lutz; Budowle, Bruce
Abstract: The current state of validation and implementation strategies of massively parallel sequencing (MPS) technology for the analysis of STR markers for forensic genetics use is described, covering the topics of the current catalog of commercial MPS‐STR panels, leading MPS‐platforms, and MPS‐STR data analysis tools. In addition, the developmental and internal validation studies carried out to date to evaluate reliability, sensitivity, mixture analysis, concordance, and the ability to analyze challenged samples are summarized. The results of various MPS‐STR population studies that showed a large number of new STR sequence variants that increase the power of discrimination in several forensically relevant loci are also presented. Finally, various initiatives developed by several international projects and standardization (or guidelines) groups to facilitate application of MPS technology for STR marker analyses are discussed in regard to promoting a standard STR sequence nomenclature, performing population studies to detect sequence variants, and developing a universal system to translate sequence variants into a simple STR nomenclature (numbers and letters) compatible with national STR databases.